The Legacy of Corrado Gini in Survey Sampling and Inequality Theory - Tillé, Yves (My University, 2016)
We present two seminal contributions of Corrado Gini on the theory of survey sampling and the theory of inequalities: the idea of balanced sampling and the Gini inequality index. These contributions have contributed to the development of a fertile field of research.
Keywords: Balanced samplingGini indexHistory of statisticsVariance estimation